(untitled) (International Journal of Engineering and Computer Science, 2013)
Several voting algorithms have been described to arbitrate the results of redundant modules in fault-tolerant systems. A voting scheme based on fuzzy set theory was introduced which softens the harsh behavior of the inexact majority voter in the neighborhood of the ‘voter threshold’ and handles uncertainty and some multiple error cases in the region defined by the fuzzy input variables. A set of fuzzy rules determines a single fuzzy agreeability value for each individual input which describes how well it matches the other inputs. Automatic fuzzy parameter selection based dynamic fuzzy voter for safety critical systems with limited system knowledge. Existing fuzzy voters for controlling safety critical systems and sensor fusion are surveyed and safety performance is empirically evaluated. The major limitation identified in the existing fuzzy voters is the static fuzzy parameter selection. Optimally selected static fuzzy parameters work only for a particular set of data with the known data ranges. Dynamic voter is designed in such a way that it can be plugged in and used in any safety critical system without having any knowledge regarding the data produced and their ranges.